Personal Branding Sherly Annavita Rahmi di Media Sosial YouTube - Zakiyah, Kiki; Wibawa, Darajat; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to find out how to form 1) Consictency (Consistency), 2) Specialization (Specialization), 3) Relevant (Relevant), 4) Distinctiveness (Differences) personal branding Sherly Annavita Rahmi through social media YouTube. The study is based on the selection of models that are relevant to what will be discussed. This study refers to the authentic personal branding model of Hubert K. Rampersad. The results showed that Sherly Annavita Rahmi's personal branding form through YouTube social media through four main criteria, namely: 1) Consistency: the content that Sherly and the team create is always the same as her character and the content upload period is always consistent. 2) Specialization: Sherly specializes as a millennial influencer, academic, and entrepreneur. 3) Relevant: the audience considers the message Sherly conveys to be relevant to the current state of affairs. 4) Distinctiveness: unlike millennial influencers, Sherly doesn't want to be considered a feminist, Sherly stands on her own feet, and has her own style of speech and language style.